A City-Wide Approach to Carbon Finance - World Bank (Washington, DC, 2017)
Urbanization and climate change will define much of the 21st century. Urbanization leads to improvement in standards of living, and through the increased density and service delivery efficiency of cities, higher growth can be achieved with lower greenhouse gas emissions. Cities and urban agglomerations house more than 50 percent of the global population and contribute more than 70 percent of Global greenhouse (GHG) emissions. As the share of urban population grows, sustainable urban development emerges as an essential component in addressing climate change. Mitigation often comes at a significant cost. Carbon finance has an important role to play in reducing these costs. Carbon finance is accessible through regulated mechanisms, such as the Clean Development Mechanism (CDM) and Joint Implementation (JI) under the Kyoto Protocol, and through voluntary markets, using the voluntary carbon standard and climate exchanges. City authorities, however, have not been able to fully access market mechanisms for carbon credits.